2014
DOI: 10.1088/0004-6256/148/4/59
|View full text |Cite
|
Sign up to set email alerts
|

PROBING FOR EXOPLANETS HIDING IN DUSTY DEBRIS DISKS: DISK IMAGING, CHARACTERIZATION, AND EXPLORATION WITHHST/STIS MULTI-ROLL CORONAGRAPHY

Abstract: Spatially resolved scattered-light images of circumstellar debris in exoplanetary systems constrain the physical properties and orbits of the dust particles in these systems. They also inform on co-orbiting (but unseen) planets, the systemic architectures, and forces perturbing the starlight-scattering circumstellar material. Using HST/STIS broadband optical coronagraphy, we have completed the observational phase of a program to study the spatial distribution of dust in a sample of ten circumstellar debris sys… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

35
290
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 206 publications
(335 citation statements)
references
References 109 publications
35
290
5
Order By: Relevance
“…Another asymmetric feature is seen on the east side up to 8 arcsec, but can not be easily related to the structures seen with SPHERE. Different asymmetries at different scales have already been noticed for HD 106906 (Kalas et al 2015) and HD 32297 (Esposito et al 2014;Schneider et al 2014) for example. One candidate companion (#1, see Appendix B) could lie within the structures revealed by STIS and the arc seen with SPHERE.…”
Section: Discussionmentioning
confidence: 80%
“…Another asymmetric feature is seen on the east side up to 8 arcsec, but can not be easily related to the structures seen with SPHERE. Different asymmetries at different scales have already been noticed for HD 106906 (Kalas et al 2015) and HD 32297 (Esposito et al 2014;Schneider et al 2014) for example. One candidate companion (#1, see Appendix B) could lie within the structures revealed by STIS and the arc seen with SPHERE.…”
Section: Discussionmentioning
confidence: 80%
“…Later on, Shen et al (2009) showed that the results from Graham et al (2007) can be reproduced by a distribution of sphere cluster aggregates with size distribution index −3.5, volume-equivalent radii between 0.1 and 0.4 µm, and a porosity of 60%. In this work, our models are compared with the optical and near-IR surface brightness profiles from Fitzgerald et al (2007) and Schneider et al (2014) and with the measured degree of polarisation from Graham et al (2007). Since our modelling deals with axisymmetric discs, all observed profiles had been averaged over the SE and NW disc sides in order to remove the observed surface brightness anomalies.…”
Section: Scattered Lightmentioning
confidence: 99%
“…To account for the extended halo of small particles, the flux was integrated up to stellocentric distances of r = 150 au for each line of sight. We also compared with the radial profiles extracted from the high-resolution HST/STIS image by Schneider et al (2014). In their Fig.…”
Section: Impact On Scattered Lightmentioning
confidence: 99%
See 1 more Smart Citation
“…Other debris disk systems with exterior massive perturbers are likely not uncommon; surveys indicate that~25% of debris disks exist in binary or triple star systems (Rodriguez & Zuckerman 2012). Planetary-mass exterior companions like HD 106906b may be responsible for the asymmetries in observed debris disks such as HD 61005 (Hines et al 2007;Esposito et al 2016) and HD 15115 (Rodigas et al 2012;Schneider et al 2014;MacGregor et al 2015), for example.…”
mentioning
confidence: 99%